A multidimensional approach to working time - Steinmetz, Holger; Justus Liebig University Giessen (My University, 2007)
In this dissertation, I propose four dimensions that serve to describe working time and that constitute the various working time schedules (e.g., part-time, shift-work, compressed work weeks). These are the (i) working time duration (i.e., how long does the individual work), (ii) the mean time of day (i.e., at which time of the day does the individual work, on average), (iii) the working time variation (is the working time stable or fluctuating within a certain period), and (iv) the number of shifts (i.e., how often does the individual work within the period). In the first place, the multidimensional approach is a descriptive attempt as every individual s working time can be located within the four dimensions. For instance, rotating shift work is primarily characterized by a late mean time of day, high variation, and moderate duration. Consequently, the multidimensional approach serves to integrate the different working time literatures. Second, my argument is that these four dimensions are the relevant causal factors that lead to consequences of working time (e.g., work-home interference, ill-health, or decrements in job performance). After a brief introduction of prominent working time schedules, I describe an empirical investigation using a sample of 387 employees from the German working population. Accordingly, one study (chapter 6) analyzed with structural equation modeling the relationship between the four working time dimensions and work-home interference and between work-home interference and further consequences (depression, job satisfaction, turnover motivation, and job performance). As a second aim, this study investigated if the relationship between the working time dimensions and work-home interference were moderated by gender, partner status (i.e., living together with a partner or not), child status (i.e., being parent or non-parent), and schedule autonomy (i.e., having the opportunity to influence working time). The results showed significant relationships between work-home interference and working time duration, mean time of day, and variation. Furthermore, work-home interference was significantly related to depression, job satisfaction, turnover motivation, and two job performance dimensions (meeting deadlines and quality). Finally, the associations between working time and work-home interference were not moderated by gender, partner and child status and schedule autonomy. The second study (chapter 7) investigated the relationship between duration, mean time of day, variation, and two job stressors (time pressure and role ambiguity) and ill-health. The results suggested significant relationships for mean time of day, duration, and role ambiguity. Surprisingly, the relationship between duration and ill-health was negative, indicating better health for individuals working long hours. The third study (chapter 8) longitudinally investigated antecedents (working time duration and job stressors) and outcomes of work-home interference (depression and turnover motivation). The results of this study showed a synchronous (i.e., short-term) effect of duration on work-home interference. Furthermore, this study revealed a cyclical model with a job stressors -> depression -> work-home interference -> job stressors pathway.

In dieser Dissertation werden vier Dimensionen vorgeschlagen, die bezwecken, den Themenkomplex Arbeitszeit zu beschreiben und die die existierenden Arbeitszeitmodelle (z.B. Teilzeit, Schichtarbeit, komprimierte Arbeitszeit) konstituieren. Dies sind (i) die Dauer der Arbeitszeit (z.B. Wochenarbeitszeit), (ii) die mittlere Tageszeit (d.h. wann am Tag arbeitet die Person), (iii) die Variation der Arbeitszeit innerhalb einer bestimmten Periode, und (iv) die Anzahl der Schichten in der Periode. In erster Linie ist der Zweck dieses multidimensionalen Ansatzes ein deskriptiver, da sich die Arbeitszeit einer Person damit innerhalb des vierdimensionalen Raums beschreiben lassen. Z.B. ist rotierende Arbeitszeit charakterisiert durch eine späte Tageszeit und hohe Variation. Somit dient der multidimensionale Ansatz zur Integration der verschiedenen Forschungszweige, die sich isoliert auf einzelne Arbeitszeitmodelle konzentrieren. Zweitens wird das Argument vertreten, dass die genannten Dimensionen diejenigen kausalen Faktoren sind, die Wirkungen der Arbeitszeit (z.B. Krankheit, oder Schwierigkeiten der Vereinbarkeit zwischen Beruf und Privatleben) hervorrufen. Nach einer kurzen Einführung in die gängigen Arbeitszeitmodelle wird eine empirische Untersuchung mit 387 Erwerbstätigen aus der deutschen Allgemeinbevölkerung beschrieben. Eine Studie (Kapitel 6) analysiert dabei mittels linearen Strukturgleichungsmodellen die Beziehung zwischen den vier Arbeitszeitdimensionen und work-home interference und weiteren Konsequenzen (Depression, Arbeitszufriedenheit, Kündigungsmotivation und Arbeitsleistung). Negative Affektivität wurde als Dispositionsfaktor in der Modell integriert. Weiterhin untersuchte diese Studie, ob die Beziehungen zwischen den Arbeitszeitdimensionen und work-home interference moderiert wurden durch Geschlecht, Partnerstatus (d.h. hat die Person einen Partner), und Elternstatus (hat die Person Kinder) und Zeitautonomie (d.h. kann die Person Einfluss auf ihre Arbeitszeiten nehmen). Dies wurde mittels multigroup Analysen und latenten Interaktionsmodellen geprüft. Die Studie ergab signifikante Zusammenhänge zwischen drei Arbeitszeitdimensionen (Dauer, mittlere Tageszeit und Variation) und work-home interference. Weiterhin war work-home interference assoziiert mit Arbeitszufriedenheit, Depression, Kündigungsmotivation und zwei Leistungsdimensionen (Einhalten von deadlines und Qualität). Die Moderatoranalysen ergaben keinerlei Modertoreneffekte der Variablen Geschlecht, Partner- und Elternstatus und Zeitautonomie. Die zweite Studie (Kapitel 7) untersuchte die Beziehung zwischen Arbeitszeitdauer, mittlerer Tageszeit, Variation und zwei Stressoren (Zeitdruck und Rollenambiguität) auf der einen Seite und strain (affektiver und körperlicher Überbeanspruchung) auf der anderen. Die Ergebnisse zeigten signifikante Ergebnisse für mittlere Tageszeit und Rollenambiguität. Überaschenderweise war die Beziehung zwischen der Arbeitszeitdauer und strain negativ, was auf einen Selektionseffekt hinweisen könnte. Die dritte Studie (Kapitel 8) untersuchte längsschnittlich mit latenten panel-Modellen die Beziehungen zwischen Antezedenzen (Arbeitszeitdauer und Stressoren und Wirkungen (Depressionen und Kündigungsmotivation) von work-home interference. Dabei wurden mehrere Alternativmodelle, die unterschiedliche kausale Richtungen postulieren, miteinander verglichen. Die Ergebnisse wiesen auf ein zyklisches Modell mit einem Stressor -> Depressionen -> work-home interference -> Stressoren Kreislauf hin. Weiterhin hatte Arbeitszeitdauer einen Effekt auf work-home interference und work-home interference einen Effekt auf Kündigungsmotivation.
Ein multidimensionaler Ansatz zur Arbeitszeit
Keywords: Arbeitszeit; Schichtarbeit; work-family conflict; work-life-balance; Stress; Working time; shiftwork; work-family conflict; work-life balance; stress; ddc:150